The Cambridge companion to biblical interpretation - Barton, John (Cambridge companions to religion, 1998)
This book provides the first complete guide for students to the present state of biblical studies. The twenty-one specially commissioned chapters are written by established scholars from North America and Britain, and represent both traditional and contemporary points of view. The chapters in Part One cover all the methods and approaches currently practised in the academic study of the Bible, while those in Part Two examine the major categories of books in the Bible from the perspective of recent scholarship - e.g. historical books of the Old Testament, Gospels, prophetic literature. Major issues raised are: the relation of modern 'critical' study of the Bible to 'pre-critical' and 'post-critical' approaches; the place of history in the study of the Bible; feminist, liberationist and new historicist concerns; the relation of Christian and Jewish scholarship; and recent interest in the Bible as literature.